The Development of Derivative Method analysis 1,4 Benzodiazepines in Biological Matrix using High-Performance Liquid Chromatography (HPLC) and Liquid Chromatography-Mass - Annisa Larasati Putri; supandi supandi; Umar Mansur (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2022)
1.4 benzodiazepine derivatives are the benzodiazepine class that is used most frequently in clinical as a sedation agent, anxiolytic, and antiepileptic. The high tense of benzodiazepine consumption can causes addiction and misappropriation. That matter causes benzodiazepine and its metabolites often find in toxicology clinical and forensic. This systematic review aimed to identify an efficient sample preparation procedure and an accurate analysis method to determine benzodiazepine existence in various biological matrices. According to the PRISMA flow diagram’s chart, twenty-four reviewed articles systematically pointed that plasma and urine utilization gave good accuracy results and recovery than other biological matrices. SBSE extraction method development using vinylpyrrolidone ethylene glycol dimethacrylate polymer gave efficient results with the amount of recovery 96%, and HPLC instrument utilization was still selective and sensitive with LOD until 12ng/ml and LOQ 36 ng/ml.